Life on board ship and cultural intimacy. Notes from the Central Mediterranean - Jasmine Iozzelli (Archivio Antropologico Mediterraneo)
In this essay, I offer reflections that emerged from my ethnographic research on board search and rescue ships in the Central Mediterranean between 2019 and 2021. I previously outlined the theoretical and epistemological foundations for these thoughts, initially in the context of the project “Ermenautica. Saperi in Rotta” at Sapienza - University of Rome and later as part of my doctoral studies in anthropology at the University of Turin. Today, different “currents” – cultural, political, and symbolic – cross the Mediterranean. When they meet aboard seagoing vessels, these currents construct a highly diverse range of shared spaces.Exploring both the macro-structure and some of the micro-practices that constitute these spaces, I attempt to point up some of the contradictions – between humanitarian logic and activist demands, between efficiency and processes of dehumanization, between formal rationality and the unpredictability of events – that arise in the construction of a sense of belonging on board a large SAR ship.